2014
DOI: 10.1080/10255842.2014.974578
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of wave propagation in a realistic model of the human external ear

Abstract: In this study, a numerical investigation is performed to evaluate the effects of high-pressure sinusoidal and blast wave's propagation around and inside of a human external ear. A series of computed tomography images are used to reconstruct a realistic three-dimensional (3D) model of a human ear canal and the auricle. The airflow field is then computed by solving the governing differential equations in the time domain using a computational fluid dynamics software. An unsteady algorithm is used to obtain the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…20 Fadaei et al applied this method to investigate the high-pressure sinusoidal and blast wave propagation in the EC. 7 The findings revealed that frequency plays a key role in the pressure distribution within the EC. At a frequency of 4 kHz, the pressure magnitude is increased significantly within the EC than adjacent frequencies.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…20 Fadaei et al applied this method to investigate the high-pressure sinusoidal and blast wave propagation in the EC. 7 The findings revealed that frequency plays a key role in the pressure distribution within the EC. At a frequency of 4 kHz, the pressure magnitude is increased significantly within the EC than adjacent frequencies.…”
mentioning
confidence: 95%
“…At a frequency of 4 kHz, the pressure magnitude is increased significantly within the EC than adjacent frequencies. 7 Garcia-Gonzalez et al investigated the interactions between the tympanic cavity, EC, and TM and found that the presence of the tympanic cavity introduces a second resonance in middle ear transfer functions at >3 kHz. 21 Qi et al studied a 3D nonlinear FE model of a 22-day-old newborn EC and concluded that the newborn EC wall is not rigid, as assessed by tympanometry.…”
mentioning
confidence: 99%